Comparative analysis of Vibrio cholerae isolates from Ghana reveals variations in genome architecture and adaptation of outbreak and environmental strains - Adade, Nana Eghele; Aniweh, Yaw; Mosi, Lydia; Valvano, Miguel A.; Duodu, Samuel; Ahator, Stephen Dela (Frontiers in Microbiology, 2022)
Recurrent epidemics of cholera denote robust adaptive mechanisms of Vibrio cholerae for ecological shifting and persistence despite variable stress conditions. Tracking the evolution of pathobiological traits requires comparative genomic studies of isolates from endemic areas. Here, we investigated the genetic differentiation among V. cholerae clinical and environmental isolates by highlighting the genomic divergence associated with gene decay, genome plasticity, and the acquisition of virulence and adaptive traits. The clinical isolates showed high phylogenetic relatedness due to a higher frequency of shared orthologs and fewer gene variants in contrast to the evolutionarily divergent environmental strains. Divergence of the environmental isolates is linked to extensive genomic rearrangements in regions containing mobile genetic elements resulting in numerous breakpoints, relocations, and insertions coupled with the loss of virulence determinants acf, zot, tcp, and ctx in the genomic islands. Also, four isolates possessed the CRISPR-Cas systems with spacers specific for Vibrio phages and plasmids. Genome synteny and homology analysis of the CRISPR-Cas systems suggest horizontal acquisition. The marked differences in the distribution of other phage and plasmid defense systems such as Zorya, DdmABC, DdmDE, and type-I Restriction Modification systems among the isolates indicated a higher propensity for plasmid or phage disseminated traits in the environmental isolates. Our results reveal that V. cholerae strains undergo extensive genomic rearrangements coupled with gene acquisition, reflecting their adaptation during ecological shifts and pathogenicity.